2021
DOI: 10.1002/ijc.33505
|View full text |Cite
|
Sign up to set email alerts
|

Association between hepatitis B and E virus infection and hepatocellular carcinoma risk

Abstract: The role of hepatitis E virus (HEV) in developing hepatocellular carcinoma (HCC) is unclear. Our study aimed to investigate the role of HE infection in HCC development and the effect of hepatitis B virus (HBV) and HEV coinfection on HCC risk. A hospital-based case-control study was conducted. A total of 474 eligible HCC cases and 586 control patients were successfully recruited. The fasting venous blood was collected from the patients at the first visited to hospital and HBV infection and HEV infection were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(75 reference statements)
0
10
1
Order By: Relevance
“…Interestingly, among these HCC patients, nine study participants were found to be coinfected with HBV and HEV, whereas only two patients presented with single HEV infection, indicating either the important role HEV might play in causing HCC, or as the author discusses, the higher susceptibility of HBV-infected patients to HEV infections. A contradictory study, however, did not find an increased risk of HCC after HEV superinfection in chronically HBV-infected patients, in a cohort consisting of 474 HCC patients and 586 controls [ 47 ].…”
Section: Clinical Evidence and Epidemiological Studiesmentioning
confidence: 99%
“…Interestingly, among these HCC patients, nine study participants were found to be coinfected with HBV and HEV, whereas only two patients presented with single HEV infection, indicating either the important role HEV might play in causing HCC, or as the author discusses, the higher susceptibility of HBV-infected patients to HEV infections. A contradictory study, however, did not find an increased risk of HCC after HEV superinfection in chronically HBV-infected patients, in a cohort consisting of 474 HCC patients and 586 controls [ 47 ].…”
Section: Clinical Evidence and Epidemiological Studiesmentioning
confidence: 99%
“…However, a much higher anti-HEV seropositivity rate (38.34%) was reported in the population in Guangdong, China [ 7 ]. Our previous study also demonstrated a relatively high HEV seropositivity rate in both hepatocellular carcinoma (HCC) patients (40.93%) and healthy individuals (41.81%) from Guangdong [ 8 ]. However, there are no comprehensive estimations of HEV seroprevalence in cancer patients or in each common cancer type.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that around 26% of cancer patients in eastern China were infected with HEV and that the prevalence of HEV in them was much higher than that in non-cancer patients, suggesting a positive correlation between HEV infection and cancer development, including extrahepatic cancers [ 6 ]. Our previous study also revealed that HEV exposure might abate the detrimental effect of HBV on HCC, indicating that the association between HEV exposure and cancer might be modified by other factors [ 8 ]. Nonetheless, there exists only very limited epidemiological information on the interaction between HEV exposure and other cancer risk factors in cancer populations, including HCC and extrahepatic cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] HBV infection is a critical risk factor for liver cirrhosis and HCC, 7 as it accounts for about 80% of all HCC cases worldwide and increases the risk of HCC approximately by 20 times. 8,9 Although HBV infections are effectively controlled by long-term nucleoside analog therapy, they are a public health problem in HCC carcinogenesis, with risk paralleled by the HBV virus burden. 10 It has been reported that patients with residual hepatitis B virus surface antigen (HBsAg) titers higher than 1,000 IU/mL are much more likely to suffer from HCC.…”
Section: Introductionmentioning
confidence: 99%